Ecobrick innovation: Creative solution to reduce plastic waste in Kacung Village - Isnaeni Isnaeni; Anggun Ramadhania; Larashati Yuan Pauji; Fakhri Okto Pian; Ridwan Nur Syabani; Novia Anggraini; Sofi Hartini; Nur Sholikha; Nindi Deva Anggraini; Bella Nur Khalida Hasibuan; Vika Martahayu (Universitas Muhammadiyah Magelang, 2023)
Plastic waste is a type of waste that takes a very long time to decompose. Ecobricks, as an innovation, do not aim to destroy plastic waste but to process it into useful objects with artistic value that can be integrated into everyday life. This activity aims to reduce plastic waste in the Kacung Village community. By creating ecobricks, it is hoped that the public can understand that plastic waste is a potential source for creative products. The method employed involved counseling through discussions with members of the Kacung Village Youth Organization in Kelapa District, West Bangka Regency. Additionally, another strategy includes direct education and coaching for youth organizations in making ecobricks. As a result, the people of Kacung Village have successfully grasped the importance of managing plastic waste through ecobrick production. Furthermore, they have been able to produce ecobrick items, such as chairs and village gates.